Geoecologia da paisagem em bacias hidrográficas do litoral oriental do estado do Maranhão, Brasil: bases para o planejamento e gestão ambiental - Machado, Adilson Matheus Borges (2022)
Anthropic activities have shown strong expansion in recent decades, causing impacts and changes in natural landscapes. These changes can be evidenced through the Geoecology of Landscape that provides subsidies for the diagnosis of anthropic impacts on territorial limits of geographic space, seeking an integrated understanding of the environment. In this perspective, this research aims to analyze the dynamics of the Watersheds of the Eastern Coast of Maranhão (BHLOM), with the overall objective of analyzing the environmental and socioeconomic dynamics of the BHLOM, in an interdisciplinary approach from the concepts of Landscape Geoecology. The methodologies used allow the understanding of the geoenvironmental dynamics of the area and also the realization of a geoecological analysis as a subsidy to environmental planning, from different investigated axes. The first axis shows the natural potentials (hypsometry, slope, soils, vegetation, water resources, geology and geomorphology). The predominant soil classes in the BHLOM are the Ortic Thiomorphic Gleissols and the Ortic Quartz Neosols. The rainfall regime presents an average annual rainfall that reaches approximately 1,800 mm. The second axis brings the investigation, through the morphometric characteristics and through the prioritization methodology, the priority basins. The maximum frequency of channels is of first order, the region has a mostly flat relief. The Periá River Watershed System receives the highest priority classification with a composite parameter value (-44.225) and the lowest priority classification (classification 8) was assigned to the Anajatuba River Watershed System with a value of 68.644. In the third axis a socioeconomic characterization and its relations with the dynamics of land use and land cover in the BHLOM was performed. The analyses showed that the municipalities of coverage presented low values of social, economic and environmental development. In the fourth axis the spatial-temporal dynamics of land use and land cover patterns was evaluated, showing that the forest formation class and dunes were predominant in the three years analyzed. The main changes were driven by vegetation suppression due to conversion by eucalyptus forestry. In the fifth axis, the BHLOM were compartmentalized using the integrated Landscape Geoecology approach, with the analysis 4 geoecological units and 9 subunits were identified: coastal sea; coastal plain (beach and post-beach, dune field, deflation plains, fluviomarine plain); fluvial and lacustrine plain (fluvial plain in the upper, middle and lower reaches of the basins, fluviolacustrine and lacustrine plains); and tablelands (barreirinhas precoastal tablelands and subcoastal tablelands) presenting the dynamic-evolutionary evaluation of the landscape development patterns. The results obtained in this study show that some interventions are still necessary from the propositional point of view, pending a better management and planning that should aim at improving land use through the implementation of effective measures of environmental protection. Thus, the socio-environmental and economic information associated with the holistic view of the geoecology of the landscape of the BHLOMs is indispensable because it provides subsidies to achieve improvements in environmental management, strengthening the socio-environmental indicators of each watershed from the proposition of guidelines for effective environmental planning at the municipal level.